Evaluation of multidisciplinary education on diet modification and fluid intake restriction adherence among chronic kidney disease patients in hemodialysis unit of general hospital in Kuantan - Sowtali, Siti Noorkhairina; Abd Ghani, Nor Amalina (2019)
Chronic kidney disease (CKD) is defined as gradual impairment of kidney function and permanent progression to end-stage renal disease (ESRD), which currently leading the public health problem affecting approximately 11.0-13.0% overall population globally (Zhang et al., 2012, Arora et al., 2013 & Hoerger et al., 2015). The large prevalence of earlier stages of CKD and rising incidence of renal failure treated with dialysis and has been a big concern (Bujang et al., 2017). Johnson et al. (2013) and Williams, Manias & Walker (2008) suggested structured, comprehensive and early education on CKD management particularly for patients with diabetes, obesity, hypertension, smoking and other risk which may delay the progress of CKD. Therefore, there is a need to evaluate the adherence and satisfaction level on education received by the CKD patients.